A critical review of diffusive gradients in thin films technique for measuring organic pollutants: Potential limitations, application to solid phases, and combination with bioassays. (January 2022) - Ji, Xiaowen; Challis, Jonathan K.; Brinkmann, Markus
Abstract: Diffusive gradient in thin films (DGT) for organics has received considerable attention for studying the chemical dynamics of various organic pollutants in the environment. This review investigates current limitations of DGT for organics and identifies several research gaps for future studies. The application of a protective outer filter membrane has been recommended for most DGT applications, however, important questions regarding longer lag times due to significant interaction or adsorption of specific groups of compounds on the outer membrane remain. A modified DGT configuration has been developed that uses the diffusive gel as the outer membrane without the use of an extra filter membrane, however use of this configuration, while largely successful, remains limited. Biofouling has been a concern when using DGT for metals; however, effect on the performance of DGT for organics needs to be systemically studied. Storage stability of compounds on intact DGT samplers has been assessed in select studies and that data is synthesized here. DGT has been used to describe the kinetic desorption of antibiotics from soils and biosolids based on the soil/biosolid physical-chemical characteristics, yet applications remain limited and requires further research before wide-scale adoption is recommended. Finally, DGT for organics has been rarely, albeit successfully, combined with bioassays as well as in vivo bioaccumulation studies in zebrafish. Studies using DGT combined with bioassays to predict the adverse effects of environmental mixtures on aquatic or terrestrial biota are discussed here and should be considered for future research. Graphical abstract: Image 1 Highlights: Current limitations of DGT samplers for organic pollutants are reviewed. Lag times introduced by filter membranes require further study and optimization of diffusive and filter membrane materials. Storage of DGT samplers needs to be optimized for unstable compounds. DIFS model can effectively describe desorption processes from the solid phase to porewater in soils and sediments. More combinations of DGT samplers and bioassays need to be developed.